Sialic acid and platelet count regulation: Implications in immune thrombocytopenia. Issue 3 (8th April 2022) - Lee‐Sundlov, Melissa M.; Rivadeneyra, Leonardo; Falet, Hervé; Hoffmeister, Karin M.
Abstract: Platelets are blood components that survive in circulation for 7 to 10 days in humans. Thus, platelet production by bone marrow (BM) megakaryocytes (MKs), and their removal from the blood circulation is precisely orchestrated to maintain an average platelet count. Abnormalities in both processes can result in thrombocytopenia (low platelet count) or thrombocytosis (high platelet count), often associated with the risk of bleeding or overt thrombus formation, respectively. Platelet glycans, particularly sialic acids, are indicators of platelet count. Loss of platelet sialic acids leads to platelet clearance. A State‐of‐the‐Art lecture titled "Platelet and Megakaryocyte Glycobiology" was presented at the ISTH virtual congress 2021 to discuss (i) the loss of O‐glycan sialic acid on BM MKs, revealing the Thomsen‐Friedenreich (TF) antigen as a new concept of thrombocytopenia; herein, impaired thrombopoiesis is attributed to activation of immune cells with a plasmacytoid dendritic cell signature; and (ii) upregulation of antibodies against the TF antigen in pediatric patients with immune thrombocytopenia (ITP), positing that glycan alterations such as MK asialylation can lead to immune cell responses. Here, we discuss our findings alongside new data presented at the 2020 and 2021 ISTH congresses on the role of sialic acids and glycans in regulating platelet count. Desialylation is a prominent feature in thrombocytopenia, notably in ITP presentation. We compare similarities between ITP mediated with shear‐stress and with storage‐related asialylation. We also discuss genes involved in sialic acid synthesis leading to thrombocytopenia. Increased awareness in gene‐regulating MK and platelet glycans is a giant leap to understanding the underpinning mechanisms of ITP and other forms of thrombocytopenia.